2005
DOI: 10.1002/aoc.847
|View full text |Cite
|
Sign up to set email alerts
|

Di(ptert‐butylphenyl)‐N,N‐di‐(iso‐butyl)carbamoylmethylphosphine oxide and its organotin and uranyl adducts: structural and spectroscopic characterization

Abstract: The single-crystal structure of the hydrophobic actinide extractant di(p-tert-butylphenyl)-N,N-di-(isobutyl)carbamoylmethylphosphine oxide (CMPO, 1) has been determined, as has that of its 1 : 1 chelate complex with uranyl nitrate (2), its 1 : 1 monodentate complexes with Ph 3 SnCl (3) and Me 2 SnCl 2 (4) bonding via the P O group. A 1 : 1 bidentate complex with Ph 2 SnCl 2 bonding via both P O and C O functionalities (5) was obtained which in solution exhibits a C O → Sn bond dissociation to exist as the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Crystal data (C 6 Our interest for organotin(IV) compounds (Sarr et al, 2013a,b) is related to applications found in various fields like in medicine, industry or agriculture (Evans & Karpel, 1985;Kapoor et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal data (C 6 Our interest for organotin(IV) compounds (Sarr et al, 2013a,b) is related to applications found in various fields like in medicine, industry or agriculture (Evans & Karpel, 1985;Kapoor et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…For applications of organotin(IV) compounds, see: Evans & Karpel (1985); Kapoor et al (2005). For compounds containing the [Sn(C 6 H 5 ) 2 Cl 4 ] 2À anion in a cis or transconformation, see: Garcia-Seijo et al (2001); Fernandez et al (2002); Venkatraman et al (2004); Diop et al (2011).…”
Section: Related Literaturementioning
confidence: 99%
“…Crystal data (C 12 Research on organotin derivatives has been an attractive area because of their numerous applications and their versatile structure (Evans & Karpel, 1985;Kapoor et al, 2005;Zhang et al, 2006;Yin & Wang, 2004;Gielen et al, 1995). In the scope of our research work on the coordination ability of oxyanions (Diop et al, 2002, Diallo et al, 2009Diop et al, 2003) and our interest to synthesize new organotin derivatives for biological tests, we elucidate here the structure of the title compound, [C 15 H 21 O 6 P 2 Sn,C 12 H 24 N] (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For related organotin derivatives, see: Weakley (1976); Molloy et al (1981); Evans & Karpel (1985); Gielen et al (1995); Yin & Wang (2004); Kapoor et al (2005); Zhang et al (2006). For our recent work on the coordination ability of oxyanions, see: Diop et al (2002Diop et al ( , 2003; Diallo et al (2009).…”
Section: Related Literaturementioning
confidence: 99%
“…Applications of organotin (IV) compounds are very well known (Evans and Karpel , 1985 ;Kapoor et al , 2005 ;Zhang et al, 2006). The mononuclear derivatives of the general formula [R 4 N] [AO 4 SnPh 3 ] (A = S, Se, Cr, W) have been synthesized and studied spectroscopically by our group (Gueye et al , 1993 ;Sall et al , 1995 ;Diop et al, 2000Diop et al, , 2002De Barros et al , 2009Diallo et al , 2009a,b ;Qamar -Kane et al, 2009 ;Fall et al, 2010), but dealing with their SnMe 3 residue containing homologue, to the best of our knowledge, only [Et 4 N] [WO 4 SnMe 3 ] has been reported (De Barros et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%